Leemos el cuento: Rosa, la llama curiosa - Cueto Mogollón, Brenda Marcela (2019)
The present professional proficiency work is based on the class sesión design, with the text comprehension competence and interest listening performance, which will result in children in Jardín de Niños N° 215 - Trujillo, show interest in communicative situations, describing the sequence of a story in three scenes and express ideas spontaneously._x000D_ On the other hand, oral expression will allow children a better interaction and integration with family, society and culture; This ability is intended to develop the ability to express one's ideas, emotions and feelings freely.